2012
DOI: 10.1155/2012/756263
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Microsatellite Instability and the Features of Sporadic Colorectal Cancer in the North Part of Iran

Abstract: Background. The aim of this study was to determine the correlation between MSI and sporadic colorectal cancer in Guilan province, North part of Iran. Materials and Methods. A total of 96 patients who underwent resection for sporadic colorectal cancer in Guilan province were studied. No patients had positive family history of cancers. The frequencies of MSI were analyzed by testing the BAT-26 and BAT-25 markers. Results. MSI analysis revealed that 22.9% of the tumors (22 patients) were microsatellite instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…On the contrary, Faghani et al [ 25 ] found that there was no a statistically significant correlation between MSI and patients’ age, this can be explained by that their study was designed to determine the correlation between MSI and sporadic cases only.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the contrary, Faghani et al [ 25 ] found that there was no a statistically significant correlation between MSI and patients’ age, this can be explained by that their study was designed to determine the correlation between MSI and sporadic cases only.…”
Section: Discussionmentioning
confidence: 94%
“…On the contrary, Faghani et al [ 25 ] found that 81.8% of total MSI-H had distal tumors. This is may be due to studyng only sporadic cases and analysis of MSI frequencies by testing the BAT-26 and BAT-25 markers.…”
Section: Discussionmentioning
confidence: 99%
“…The basic tests identify five markers (NR-21, BAT-26, BA T -25, NR-27 and NR-24) to devise the simplest diagnostic assay (9). Previous reports have shown significant diversity regarding the most common marker for microsatellite testing; BAT 25, BAT26 and NR21 have been reported in HNPCC and sporadic CRCs (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
“…Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers. As it shows, the frequency of MSI in patients with HNPCC has been 29% -62.5% (9-25), there are not so many studies about the frequency of MSI in sporadic CRC from Iran; however, the reported frequencies of MMR have been from 19.4% to 66.6% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
See 1 more Smart Citation